Language, enunciation, discourse. A study on the notion of subjectivity in some linguistic proposals - Savio, Karina (2022)
The purpose of this article is to locate, question and analyze what is understood by subjectivity in certain approaches coming from language studies. In this respect, representative authors have been included who are part of the enunciative tradition, and some are from discourse analysis who use enunciation to question its nature, namely: Arnauld and Lancelot, Bally, Benveniste, Jakobson, Culioli, Ducrot, Kerbrat-Orecchioni, Maingueneau and Pêcheux. This paper is organized along three axes: the definitions of enunciation established in the selected texts, the ways in which language and its articulation (or not) along with thought are understood in these elaborations, and the ways in which subjectivity(ies) circulate(s) and their implications. This journey has made it possible to identify the different conceptions related to the enunciative dimension and to the language/thought relationship that cross the theoretical developments addressed, and has recognized two ways of thinking about subjectivity: a constituent subjectivity, in which the subject is cause, origin; and a constituted subjectivity, in which the subject is effect. However, there are various nuances that distinguish the different proposals.